New species and records of Angolan Limnichidae (Coleoptera: Byrrhoidea) - Matsumoto, Keita (Zootaxa, 2021)
Two new species of Limnichidae, Simplocarina angolensis Matsumoto sp. nov. and Byrrhinus angolensis Matsumoto sp. nov. are described. Simplocarina curticollis Pic, 1922 is reported as a new genus and species for the fauna of Angola.